Стихи и рассказы о Родине: [сборник : для среднего школьного возраста / художники: Е. Володькина и др.] - Володькина Елена Михайловна (РОСМЭН, 2015)
Экземпляры: Д.О. (20201116) / Инвентарный номер: 48088 / Цена: 197.60 / Авт.знак: С 80 / ГРНТИ: 17.82 / ББК: 84(2=411.2)